Tocar el fondo a un chasquido de dedos. Aproximaciones a las características del estilo interpretativo en las agencias de noticias - González Lemes, Ivet; Brizuela Brínguez, Luis; González Borges, María De Los Ángeles (Estudios sobre el Mensaje Periodístico, 2008)
In this article we analyze the ways that tradicional news agencies, like AP, AFP, EFE and Reuters, use nowadays interpretative journalistic style. We also took into account on the research the experience of Inter Press Service, a news agencie specialized on interpretative journalism. We include in the study some news agencies historic backgrounds, and analyze the relations between concepts as languages and style of news agencies.
Keywords: Journalism; News agencies; News agency languague; News agency style; Interpretative style